2019
DOI: 10.2478/ats-2019-0007
|View full text |Cite
|
Sign up to set email alerts
|

Row spacing and weed management methods influences growth and yield of soybean (Glycine max (L.) Merr.)

Abstract: Weed infestation is among the primary reasons for low yields of soybean in Nigeria and other parts of Sub Saharan Africa (SSA). Field trials were therefore carried out in 2016 and 2017 cropping seasons to evaluate the effect of row spacing and weed management methods on growth and yield of soybean. The use of 50 cm row spacing resulted in significant (P < 0.05) reduction in weed cover score, weed density and weed dry matter with subsequent increase in soybean growth and grain yield compared to 75 and 100 cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
(28 reference statements)
1
4
0
Order By: Relevance
“…This trend suggests that rapid weed growth was observed between 3 and 9 WAS in both years. This result corroborates an earlier report on the same ecology, which showed that rapid weed growth occurred between 3 and 9 WAS in a study conducted on soybean (Daramola et al, 2019b). The effect of weed control timing on the growth, yield components and yield of rice Weed control timing had a significant effect on the growth and yield of rice in 2015 and 2016 (Table 3).…”
Section: Resultssupporting
confidence: 90%
“…This trend suggests that rapid weed growth was observed between 3 and 9 WAS in both years. This result corroborates an earlier report on the same ecology, which showed that rapid weed growth occurred between 3 and 9 WAS in a study conducted on soybean (Daramola et al, 2019b). The effect of weed control timing on the growth, yield components and yield of rice Weed control timing had a significant effect on the growth and yield of rice in 2015 and 2016 (Table 3).…”
Section: Resultssupporting
confidence: 90%
“…This was possibly because of more evenly distribute rainfall experienced in 2017 than in 2016 ( Figure 1). It has been reported that rainfall affects weed species distribution and their competitiveness within a weed community (Daramola et al, 2019).…”
Section: Weed Cover Score Weed Density and Dry Weight As Affected Bymentioning
confidence: 99%
“…However, consumption growth has out-paced domestic production growth with yield stagnated at 960 kg ha -1 , leaving a supply gap of more than 1.5 million tons (Khojely et al, 2018). One of the major constraints to high soybean yield in Nigeria is weed interference (Imoloame, 2014;Daramola et al, 2019). The losses caused by weeds exceed the losses from any other category of damage like insect, pest and diseases (Oerke and Dehne, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This is however, tedious, inefficient, time consuming and associated with high labour demands (Ogwuike et al, 2014;Datta et al, 2017). In addition, labour for manual weeding is scarce and often too expensive for the average farmer to afford (Adigun et al, 2017;Daramola et al, 2019). Consequently, farmers spend a large amount of time in weeding operation (Daramola et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Herbicides reduce drudgery and protect crops from early weed competition (Rodenburg et al, 2011). However, there are not many herbicides that can control different kinds of weeds with one application, and their efficacy is further limited when they are used alone (Adigun et al, 2017;Daramola et al, 2019). They rarely provide a season-long weed control.…”
Section: Introductionmentioning
confidence: 99%